2022
DOI: 10.1002/mds.28955
|View full text |Cite
|
Sign up to set email alerts
|

Reply to: Juvenile PLA2G6‐parkinsonism due to Indian ‘Asian’ p.R741Q mutation, and response to STN DBS

Abstract: We are grateful for Ravat et al.'s interest in our article on PLA2G6-parkinsonism. 1,2,3 They reported an additional case showing some clinicoradiological diagnostic hints we highlighted, including young onset of levodopa-responsive parkinsonism, occurrence of truncal dystonia and cerebellar signs, early development of levodopa-induced dyskinesia, and presence of cerebellar atrophy as well as possible lack of iron deposition on brain MRI. 2 Their case 1 reinforces our observation that NM_003560.4(PLA2G6):c.222… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…The reported here results suggests that these characteristics are associated with the presence of a compound heterozygous mutation of the PLA2G6 gene with c.991G > T and c.1427 + 1G > A. Several studies have indicated that the rapid progression of the disease in EOPD patients may be related to the fluctuation of the hormone levels in the body (Magrinelli et al, 2022). However, this case had no obvious history of hormone fluctuations.…”
Section: Discussionmentioning
confidence: 50%
“…The reported here results suggests that these characteristics are associated with the presence of a compound heterozygous mutation of the PLA2G6 gene with c.991G > T and c.1427 + 1G > A. Several studies have indicated that the rapid progression of the disease in EOPD patients may be related to the fluctuation of the hormone levels in the body (Magrinelli et al, 2022). However, this case had no obvious history of hormone fluctuations.…”
Section: Discussionmentioning
confidence: 50%
“…Only a few authors reported levodopa‐induced OMD in a PD subject 7,8 . Besides, OMD has been reported in two cases with PLA2G6‐parkinsonism which is a recently defined, rare form of hereditary parkinsonism 9 . To our knowledge, there are only two published reports describing a PSP subject developing levodopa‐induced OMD 10,11 .…”
Section: Discussionmentioning
confidence: 96%
“…7,8 Besides, OMD has been reported in two cases with PLA2G6-parkinsonism which is a recently defined, rare form of hereditary parkinsonism. 9 To our knowledge, there are only two published reports describing a PSP subject developing levodopainduced OMD. 10,11 Tan et al reported a patient with PSP who developed levodopa-induced OMD after increasing levodopa dosage (to 300 mg/day) which completely resolved after discontinuation of levodopa.…”
Section: Discussionmentioning
confidence: 98%
“…Despite several clinical studies, e.g. [6], that have shown evidence of the effectiveness of DBS in movement disorders treatment, there are still some unresolved issues that persist. The efficacy of DBS has been shown in people with PD who do not respond to medicinal treatment, leading to improvements in both the quality of life and motor function, as previously discussed.…”
Section: Fig 2 Dbs Targets For Movement Disordermentioning
confidence: 99%